Case Report: Myomatous erythrocytosis syndrome presenting as rapid growth of an extra-uterine mass - Wang, Shao-Jing; Chen, Yun-An; Shih, Yu-Hsiang; Chen, Ming-Jer; Lu, Chien-Hsing (Frontiers in Surgery, 2022)
Objective: To report a case of myomatous erythrocytosis syndrome (MES) with an extra-uterine manifestation. Case report: A 43-year-old woman presented with progressive abdominal distension and rapid enlargement of a pelvic mass. Upon survey, a high-level of hemoglobin (19.0 g/dL) was documented. The initial impression was an ovarian malignancy, but uterine sarcoma could not be ruled out because of its rapid growth. However, during exploratory laparotomy, the pelvic mass was found to be a 31 cm broad ligament leiomyoma; which is extremely rare for its size and location. The specimen was further studied immunohistochemically, which revealed excessive expressions of erythropoietin and erythropoietin receptors in addition to the diffusely matured blood vessels in the myoma tissue. The patient’s hemoglobin level resumed to normal three months post-surgery. The diagnosis of MES was confirmed both clinically and histologically. Conclusion: A correct preoperative diagnosis is challenging when MES manifests as an extrauterine mass. The coexistence of MES should be considered in the management of all leiomyoma with polycythemia, regardless of locations.